2008
DOI: 10.1517/14728222.12.9.1097
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pituitary adenylyl cyclase-activating polypeptide (PACAP, ADCYAP1: adenylyl cyclase-activating polypeptide 1) in the treatment of schizophrenia

Abstract: Background : Deficiency of pituitary adenylyl cyclase-activating polypeptide (PACAP) and its specific receptor, PAC1, causes a schizophrenia-like phenotype in mice. In addition, the relation of the PACAP and PAC1 genes to schizophrenia has been shown by single-nucleotide polymorphism association studies. Furthermore, PACAP is reported to be involved in the function of disrupted-in-schizophrenia 1. Objective : To summarize briefly the recent evidence relating the PACAP system and schizophrenia and discuss the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 114 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…These studies indicate the presence of an interaction between the PACAP system and the dopaminergic and serotoninergic systems. In addition, it has been clearly confirmed that PACAP may play an important role in psychological disease, and that the regulation of PACAPergic signals could represent a potential target for the pharmacological treatment of such psychiatric states as schizophrenia or bipolar disease [10, 19, 29]. However, before these new drugs enter clinical practice, it is important to determine how existing neuroleptics affect the activity of the PACAPergic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies indicate the presence of an interaction between the PACAP system and the dopaminergic and serotoninergic systems. In addition, it has been clearly confirmed that PACAP may play an important role in psychological disease, and that the regulation of PACAPergic signals could represent a potential target for the pharmacological treatment of such psychiatric states as schizophrenia or bipolar disease [10, 19, 29]. However, before these new drugs enter clinical practice, it is important to determine how existing neuroleptics affect the activity of the PACAPergic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another pathophysiological phenomenon associated with schizophrenia is the abnormality in PACAPergic signals, which is present upstream of the regulation of dopaminergic, serotoninergic and glutamergic systems. The hypofunction of the PACAP system leads to the activation of the dopaminergic and serotonergic systems, and the inactivation of the glutamergic system [10]. Therefore, a potentially valuable target for schizophrenia treatment could be the regulation of PACAP receptors, though which the peptide exerts its neurotrophic and neuroprotective potency; one such destination being glial cells, which are involved in neural communication: another element attenuated in the schizophrenic brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). In human, the PACAP gene is localized to the P11 region of chromosome 18, which is associated with holoprosencephaly Chang et al, 1993;Golden, 1998) and psychiatric disorders, suggesting that PACAP might be involved in the control of brain development and/or the etiology of schizophrenia (Ishiguro et al, 2001;Kamnasaran, 2003;Hashimoto et al, 2007;Matsuzaki and Tohyama, 2008).…”
Section: The Pituitary Adenylate Cyclase-activating Polypeptide Genementioning
confidence: 99%
“…Based on its ability to activate cAMP in the pituitary gland, it acts as a neurotransmitter, neuromodulator, neurotrophic, or neuroprotective factor, via multiple signaling pathways (Das et al, 2007;Vaudry et al, 2009). PACAP has a protective role in several nervous system diseases/conditions, such as focal cerebral ischemia (Allais et al, 2010;Nakamachi et al, 2010;Stetler et al, 2010), Alzheimer's disease (Kojro et al, 2006), schizophrenia (Matsuzaki and Tohyama, 2008;Tanaka et al, 2006), anxiety disorders (Choi et al, 2008;Norrholm et al, 2005), Parkinson's disease , and TBI ( Johanson et al, 2011;Kovesdi et al, 2008;van Landeghem et al, 2007). Several reports have demonstrated that PACAP can attenuate axonal injury induced by trauma (Kovesdi et al, 2008;Tamas et al, 2006), and promote neural restoration through enhanced neurogenesis, angiogenesis, and neuroprotective effects ( Johanson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%